Nettle (Urtica dioica) leaves as a novel food: Nutritional, phytochemical profiles, and bioactivities - Anjali Sahal; Afzal Hussain; Sanjay Kumar; Ankita Dobhal; Waseem Ahmad; Khan Chand; Rishi Richa; Umesh Chandra Lohani (Food Chemistry: X)
Urtica dioica is widely distributed across temperate regions of the world and is highly beneficial and packed with nutritional value including a rich profile of phytochemicals, amino acids, and essential minerals. Due to abundance of these attributes, the nutritional, antioxidant, and antimicrobial properties of Urtica dioica were assessed systematically. Additionally, proximate, functional, antinutrient, mineral, polyphenolic compounds, FRAP, and DPPH assays were also examined. The findings revealed that Urtica dioica contains high Mg, Ca, Fe, and Zn. The examined values of DPPH and FRAP showed high antioxidant potential of Urtica dioica. UHPLC and GC–MS analysis confirmed Urtica dioica as an excellent source of phenolic and bioactive compounds. In view of these experimental findings, Urtica dioica can be incorporated into edible coatings and functional foods. Its excellent antimicrobial properties against Gram +ve and Gram -ve bacteria underscore its viability as an excellent source of functional ingredients in edible coatings.